Histological, Histomorphometrical, and Biomechanical Studies of Bone-Implanted Medical Devices: Hard Resin Embedding. (17th January 2020) - Maglio, M.; Salamanna, F.; Brogini, S.; Borsari, V.; Pagani, S.; Nicoli Aldini, N.; Giavaresi, G.; Fini, M.
Abstract : The growing incidence of degenerative musculoskeletal disorders as well as lifestyle changes has led to an increase in the surgical procedures involving implanted medical devices in orthopedics. When studying implant/tissue interface in hard materials (i.e., metals or dense plastics) and/or in large bone segments, the hard plastic embedding of the intact undecalcified tissue envelope with the implant in situ is needed. The aim of this work is to describe the advances and the possibilities of high-temperature methyl methacrylate (MMA) embedding for the histological, histomorphometrical, and biomechanical assessment of bone-implanted medical devices. Unlike routine techniques, undecalcified bone processing histology, using high-temperature MMA, requires a complex and precise sample processing methodology and the availability of sophisticated equipment and software for both sample preparation and analyses. MMA embedding permits the evaluation of biological responses to the presence of implanted medical devices without implant removal, allowing simultaneous qualitative and quantitative histological evaluation, both static and dynamic histomorphometry, and biomechanical analyses not possible with tissue decalcification. MMA embedding, despite being a demanding procedure, is still preferred to other kinds of resin-based embedding because of its peculiar characteristics, which allow the study of samples of big dimensions also implanted with hard materials without reducing the sample or removing the material. Dynamic measurements are allowed together with biomechanical investigations at the bone-biomaterial interface, obtaining a comprehensive and precise evaluation of the safety and effectiveness of medical devices for orthopedic regenerative, reconstructive, and reparative surgery.